2012
DOI: 10.1089/scd.2011.0419
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Novel Multipotent Neural Crest-Derived Stem Cells from Adult Human Inferior Turbinate

Abstract: Adult human neural crest-derived stem cells (NCSCs) are of extraordinary high plasticity and promising candidates for the use in regenerative medicine. Here we describe for the first time a novel neural crest-derived stem cell population within the respiratory epithelium of human adult inferior turbinate. In contrast to superior and middle turbinates, high amounts of source material could be isolated from human inferior turbinates. Using minimally-invasive surgery methods isolation is efficient even in older p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(178 citation statements)
references
References 49 publications
6
171
0
Order By: Relevance
“…12 Residing in the nasal cavity, OEMSCs are derived primarily from neural crest cells and possess a high proliferation rate, self-renewal capability, and multiple lineage differentiation capabilities. 13 Several studies have reported that OE-MSC transplantation can induce neurogenesis and restore hippocampal neuronal networks in mice. 14 However, it remains largely unknown whether OE-MSCs, which are similar to other types of MSCs, possess any immunoregulatory functions.…”
Section: Introductionmentioning
confidence: 99%
“…12 Residing in the nasal cavity, OEMSCs are derived primarily from neural crest cells and possess a high proliferation rate, self-renewal capability, and multiple lineage differentiation capabilities. 13 Several studies have reported that OE-MSC transplantation can induce neurogenesis and restore hippocampal neuronal networks in mice. 14 However, it remains largely unknown whether OE-MSCs, which are similar to other types of MSCs, possess any immunoregulatory functions.…”
Section: Introductionmentioning
confidence: 99%
“…Various MSCs derived from cranial neural crest are involved in corneal stromal stem cells, dental pulp, periodontal ligament, skin and hair follicles, but these MSCs have the disadvantages that their detachment requires difficult surgery, and that they have restricted life span [31]. In contrast, surgery to obtain hTMSC is minimally invasive and causes minimal physical pain to the patient; it also provides the possibility of autologous therapy [23,37]. The present paper presents the possibility of hTMSCs to differentiate into keratocyte progenitor cells after 7D of KDM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Located in the olfactory region of the nasal cavity, OM-MSCs are primarily derived from neural crest cells, have a high proliferation rate, self-renewal ability and multiple lineage diferentiation capabilities [83]. These cells have already been isolated from human and mice [84], rat [85], rabbit [86] and dog [87], both with in vivo [84] and post-mortem protocols [86].…”
Section: Isolation Characterization and Diferentiationmentioning
confidence: 99%